Pengembangan Media Interaktif Berbasis Ispring Suite pada Mata Pelajaran IPAS Kelas IV SD Negeri 106189 Sennah - Detristia, Debby; Simanihuruk, Lidia; M, Zainuddin; Mailani, Elvi; Rozi, Fahrur (Lembaga Intelektual Muda (LIM) Maluku, 2025)
The purpose of this study was to describe the feasibility, practicality, and effectiveness of interactive media based on Ispring Suite in the subject of science for grade IV of SD Negeri 106189 Sennah. This type of research uses Research and Development using the ADDIE research model. Validation by material experts was carried out in one stage with a result of 75.38%, which is included in the